Ex vitro rooting and acclimatization Micropropagated seedlings of blackberry 'Xavante' Enraizamento ex vitro e aclimatização de plântulas micropropagadas de amoreira-preta 'Xavante' - Pelizza T.R.* (2013)
The objective of this study was to evaluate the ex vitro rooting and acclimatization of blackberry 'Xavante'. This study was conducted at the Agro Veterinary Science Center (CAV / UDESC), in Lages (SC). In the stage of ex vitro rooting, higher number of roots was obtained with 320 mg.L-1 of IBA. There was positive linear correlation according to the IBA for average length of roots and total fresh weight of seedlings. In the acclimatization stage the seedlings after six months, had a higher total fresh weight with the composition of the organic substrate Tecnomax ®) + vermiculite and organic substrate Tecnomax ®. Thus, for ex vitro rooting of blackberry 'Xavante' it is recommended immersion of seedlings with IBA concentration of 320 mg L-1 for 5 minutes and indicates the use of the organic substrate Tecnomax ® to step acclimatization.